School-to-work transition challenge: a social profile of young workers in Malaysia - Abd. Rokis, Rohaiza (2011)
Introduction: School-to-work transition is indeed a confusing and difficult period for young people. Youth employability is often hindered by the fact that young people lack the right work attitude required by the employment market. The major objectives are to understand the meaning of work among young people; and to investigate the relationship between dysfunctional attitudes with decent work ethics among young people. The study hypothesis is that decent work ethics deficits among young people are associated with dysfunctional attitudes such as lack of assertiveness, self-confidence deficiency and short of the integrity. Methods, methodologies and sampling: The study applies both qualitative (N: 50) and quantitative (N: 3) approaches. The study sample was derived from the Group 1, Batch 8/2011 trainees of the Program Latihan Khidmat Negara (PLKN) or National Service Training Programme. Conclusion: Most often the study’s respondents, who are representing the Malaysian youth, experience the deficit of decent work ethics associated with dysfunctional attitudes toward work.